The Role Of The Land Office In Addressing "Absentee/Guntai" Land Ownership in Buru District - Sofyan Malik; Zubair Zubair (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
This study aims to seek the factors that cause absentee/guntai land ownership in Buru District and the role of the Buru District Land Office in overcoming or resolving the problem of absentee/guntai lands. The types and sources of data used by the author in assisting the research to be carried out are primary data and secondary data. To collect field research data the author uses the following methods: Interviews, namely data collection carried out in the form of questions and answers directly to the relevant respondents. The results of the study show that the prohibition of absentee/guntai land ownership in Buru District has not been implemented effectively. This is evidenced by the existence of absentee/guntai land ownership in Waeapo District and Lolong Guba District. The phenomenon of absentee/guntai land prohibition has actually occurred, but no strict sanctions have been imposed.